Evaluasi Program Kader Surabaya Sehat (KSH) dalam Peningkatan Perilaku Hidup Bersih dan Sehat (PHBS): Sintesis Literatur Sistematis Berbasis Model CIPP untuk Konteks Kecamatan Gunung Anyar - Renantanda Shah Alam; Agus Prastyawan; Prasetyo Isbandono; Reza Rahmadian (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The Surabaya Healthy Cadre Program is a community empowerment strategy that aims to improve Clean and Healthy Living Behaviors (PHBS) through the role of health cadres at the community level. Although this program has been widely implemented, a systematic policy evaluation is needed to assess the alignment between program objectives and achievements at the community level. This study aims to evaluate the Surabaya Healthy Cadre Program policy in improving PHBS in Gunung Anyar District using the CIPP (Context, Input, Process, Product) model through a Systematic Literature Review approach. The literature search process was conducted on various electronic databases following the PRISMA protocol, resulting in ten articles that met the inclusion criteria for in-depth analysis. The evaluation results showed that in terms of context, the program was relevant to community needs and in line with national health development policies. In terms of input, resources were considered adequate but still required capacity building for cadres through continuous training and operational support. In terms of process, program implementation proceeded according to plan, although there were variations in implementation quality between regions. In terms of product, the program showed a positive contribution to improving community PHBS, but efforts were still needed to improve the equity of outcomes, effectiveness, and sustainability of the program. These findings are expected to form the basis for evidence-based policy recommendations to strengthen public health programs.